A novel approach to neoplasms medial to the condyle: a condylectomy with anterior displacement of the condyle. Issue 4 (April 2016) - Ye, Z.-X.; Yang, C.; Chen, M.-J.; Abdelrehem, A.
Abstract: Resecting neoplasms involving the infratemporal space has a high risk of damaging critical nerves and vessels, in addition to joint form and function. The purpose of this study was to introduce a novel approach to lesions medial to the condyle, which comprises a condylectomy with anterior displacement of the condyle. The indications evaluated using digital surgical simulation, the critical surgical technique, and the preliminary clinical effects are presented here. Five cases underwent this approach between January 2006 and December 2014. The common characteristics of the five masses were (1) that they were non-malignant neoplasms involving the posterior-medial region of the condyle; (2) the upper and lower borders were between the skull base and the lingula, while the anterior border did not exceed the coronoid process. All masses were resected successfully with no damage to any critical nerves or vessels. The average follow-up period was 29.8 months (range 6–56 months). There was no recurrence, secondary deformity, or facial paralysis. The average mouth opening improved from an original 27 mm to 34 mm after surgery. The condyles were well fixed, with no resorption, as shown on computed tomography scans.